The Characteristic of Porang Flour (Amorphophallus muelleri Blume) Purification Use Ethanol and The Application as Subtitution Agent on Chicken Sausage - Yovy Ermawati, Noor Harini Sri Winarsi (Universitas Muhammadiyah Malang, 2019)
Abstract: Pouring flour contains high glucomannan which can reach 65 %. This research purposed to analyze the physical and chemical of porang flour purification use ethanol and to describe the effect of the proportion of tapioca and porang flour addition to the physical, chemical, and organoleptic of chicken sausage. Randomized Complete Block Design was applied with two-phase. The first stage was the purification process used ethanol with different concentration (60%, 75%, and 90%). The second phase was the addition of orange and tapioca flour (gram) (0:20, 1:19, 2:18, 3:17, 4:16, 5:15, 6:14), all treatment was replicated 3 times. The results of the first process showed that there was a very significant difference effect to the glucomannan, rendemen, viscosity, and color (lightness and yellowish) of pouring flour. The best treatment was the purification by ethanol 90% with 11,2 % water content, 0,78% ash content, 58,20% glucomannan, 78, 11% rendered, and 3,33 dPas viscosity. The second treatment results described that there was a very significant effect of tapioca and pouring flour addition to the water content, ash content, fat, protein, carbohydrate, color intensity (L, a+, and b+), and organoleptic (taste, aroma, appearance, and favorite product) of chicken sausage.